Recubrimiento biodegradable a base de mucílago de linaza (Linum usitatissimum) Y glicerina para la conservación de la mora de castilla (Rubus glaucus). - Laica Pilco, Tania Estefania (2020)
The Castilla blackberry (Rubus glaucus) is one of the most perishable fruits, which lasts 3 to 5 days in refrigeration, due to its high respiratory level. This research objective was to apply a biodegradable coating based on flaxseed and glycerin for the preservation Castilla blackberry, in order to prolong the conservation time, maintain quality attributes and the fruit acceptability. It had with blackberries from the Sigchos canton, in Cotopaxi province. A factorial design (AxB+1) was proposed, fruits were selected according the color and size, which were distributed in batches of 40 fruits for each treatment, washing and disinfection processes with sodium hypochlorite (150 ppm) were applied submerged for 5 minutes, then the biodegradable coating was applied by immersion and drying techniques at room temperature for 40 minutes. Four treatments were carried out with one control and two replicas. The response variables considered are: pH, titratable acidity, soluble solids, firmness, moisture, weight loss, determination of microbiological parameters (total coliforms, molds and yeasts) and organoleptic characteristics (visual quality, characteristic aroma, firmness, overall impression and taste). The variance analysis and comparison test of Tukey with a 95% confidence level in the physicalchemical and microbiological analyzes. The best coating was the treatment T2 (3% linseed mucilage + 2% glycerin) which allowed to maintain the fruit quality, because it retained the greatest amount of physicochemical and organoleptic properties during the experiment. The response variable considered of great significance is weight loss, which was recorded daily for 10 days, in this physical parameter the best treatment was T2 (3% linseed mucilage + 2% glycerin), since it lost less liquid reaching an average of 3,74%. The economic study determined that the product cost for 175g presentation is $ 1,13; and the coating cost is $ 0.08 for 40 units of default, a value that is accessible to consumers. It is concluded when using linseed mucilage and glycerin as a biodegradable coating, it allows to preserve the organoleptic characteristics, being acceptable by consumers during the sensory evaluation.